Multimodal representations of gender in young children's popular culture - Lindstrand, Fredrik; Insulander, Eva; Selander, Staffan (MedieKultur: Journal of media and communication research, 2016)
This article poses questions regarding learning and representation in relation to young children's popular culture. Focusing on gender, the article builds on multimodal, social semiotic analyses of two different media texts related to a specific brand and shows how gender and gender differences are represented multimodally in separate media contexts and in the interplay between different media. The results show that most of the semiotic resources employed in the different texts contribute in congruent ways to the representation of girls as either different from or inferior to boys. At the same time, however, excerpts from an encounter with a young girl who engages with characters from the brand in her role play are used as an example of how children actively make meaning and find strategies that subvert the repressive ideologies manifested in their everyday popular culture.